1998
DOI: 10.1111/j.1532-5415.1998.tb01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dehydroepiandrosterone Sulfate, Body Composition, and Physical Fitness in Independent Community‐Dwelling Older Men and Women

Abstract: In this group of independent community-dwelling older men, several factors were found to be associated with the serum DHEAS concentration, whereas in a group of older women, no such associations were identified with the exception of BMI. Men in the highest quartile of serum DHEAS level, compared with those with a serum DHEAS level in the lowest quartile, were younger, leaner, more fit, had higher TT and FT levels, and had a favorable lipid profile. No such differences were identified between the women in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 55 publications
5
43
2
1
Order By: Relevance
“…An increase of DHEA is less pronounced in elderly people after exercise (Malarkey et al 1993). However, findings of increased DHEA after exercise was not found in other studies in elderly women (Hersey et al 1994, Milani et al 1995, Abbasi et al 1998, Hakkinen et al 2000. Our present study indicates, that the discrepant findings might be explained by differences in body fat distribution, because only peripheral adipose women demonstrated the positive association between physical activity and plasma levels of DHEA and ASD.…”
Section: Discussionmentioning
confidence: 58%
“…An increase of DHEA is less pronounced in elderly people after exercise (Malarkey et al 1993). However, findings of increased DHEA after exercise was not found in other studies in elderly women (Hersey et al 1994, Milani et al 1995, Abbasi et al 1998, Hakkinen et al 2000. Our present study indicates, that the discrepant findings might be explained by differences in body fat distribution, because only peripheral adipose women demonstrated the positive association between physical activity and plasma levels of DHEA and ASD.…”
Section: Discussionmentioning
confidence: 58%
“…In men, the magnitude and direction of the association between DHEA-S and obesity is also equivocal. Seven studies found a significant association between plasma DHEA-S and measures of obesity (55 -61), two studies found that DHEA-S was negatively associated with measures of obesity (57,59), whereas five studies found the opposite (55,56,58,60). A number of studies also found no significant association (62 -67).…”
Section: Obesity and Body Fat Distributionmentioning
confidence: 89%
“…In the study by Abbassi et al (58), the association between DHEA-S and age was non-significant in women, which suggests that the positive association between BMI and DHEA-S was presumably independent of age in that study. Moreover, statistical adjustment for age did not abolish the negative association found in males between DHEA-S and body fat mass or percent body fat (58). Adjustment for age led to a non-significant correlation between DHEA-S and BMI in the women studied by Barrett-Connor & Ferrara (52).…”
Section: Obesity and Body Fat Distributionmentioning
confidence: 90%
See 2 more Smart Citations